A Field Defining Study. Cătălina Gheorghiu Iliescu, “Un model polisistemic de analiză comparativă a textului dramatic din perspectiva traductologiei descriptive (A Polysistemic Model of Comparative Analysis of the Dramatic Text from the Perspective of Descriptive Translation Studies)“ (București: Editura Universității din București, 2018) - RĂDULESCU, Domnica (Studia Universitatis Babeș-Bolyai Dramatica, 2019)
Cătălina Iliescu Gheorghiu’s recent book Un Model Polisistemic de analiza comparativa a textului dramatic din perspectiva traductologiei descriptive (A Polysistemic Model of Comparative Analysis of the Dramatic Text from the Perspective of Descriptive Translation Studies) is a meticulously crafted and unprecedented comparative study of two translations of the play The Third Stake by the celebrated Romanian writer Marin Sorescu within the theoretical frame of the model for descriptive and functional translation studies created by Jose Lambert and Hendrik Van-Gorp.